Creation of product-service systems (PSS) proposals in the fuzzy front-end - Barquet, Ana Paula Bezerra (2015)
Product-service systems (PSS), defined as a system of products, services, infrastructure, and networks that aims to satisfy customer needs, support business innovation and has the potential to lead to improved environmental performance. The adoption of PSS requires modifications in the business model of companies or even the creation of new ones. The decision to modify or create business models occurs in the fuzzy front-end through the development of proposals. In this sense, the creation of PSS proposals might assist the adoption of PSS business models in enterprises. However, companies still need support to adopt PSS business models due to three main reasons. First, most of the studies about PSS business models mention its importance but do not explore which content should compose such models. Second, PSS business models are explored considering a partial view of business model dimensions. Finally, there is a lack of methods and tools that support the adoption of PSS business models in the fuzzy front-end. Thereby, the aim of this study is to develop a method, named Configurator of PSS Proposals, to cope with these challenges and assist the creation of PSS proposals for current or new business models. By means of systematic literature review, consulting with experts and an explorative case study, the method was developed. It is composed by eight steps and each step addresses a business model dimension, e.g. value proposition. The steps encompass a range of tasks that must be performed in order to create a PSS proposal. To support carrying out the tasks, a help element is available. This help contains additional information to support the utilization of the method, such as: examples of companies that adopted PSS and hints of practices, methods and tools. To evaluate the method, it was applied through a case study in the context of a research project. The aim was to create a PSS proposal for a bicycle concept and verify whether the method reach its purpose, i.e. is able to support the creation of a PSS proposal. Final considerations include contributions and limitations of this study. An example of contribution of the method is provision of a shared knowledge about PSS between different areas of expertise. As limitation, the lack of application of the method in a real case is highlighted. Additionally, future research is addressed based mainly on the insights gathered in the second case study, e.g. the inclusion of new tasks and relations between them.